Phenology and productivity of elephant-foot yam (Amorphophallus paeoniifolius) in relation to planting time under humid tropical conditions (Current Horticulture, 2024)
Phenology and productivity of elephant foot yam [Amorphophallus paeoniifolius (Dennst.) Nicolson] were studied by planting its varieties, Gajendra and Sree Padma, under humid tropical conditions of Kerala by planting them during February, March and April during 2014, 2015 and 2016 at ICAR-CTCRI, Thiruvananthapuram. Gajendra took 23-90 days for sprouting, 65-114 days for tuber initiation, 195-261 days for senescence, which lasted for 25-64 days, while Sree Padma took 22-64 days for sprouting, 69 days for tuber initiation, 195-263 days for senescence lasting for 28-64 days during different seasons. Active tuber development was noticed between 3 to 6 months after planting. Timely planting resulted in more and comparable tuber yield both in Gajendra and Sree Padma (27.8 and 27.2 Tonnes/ha). Delayed planting although resulted in early emergence and tuber initiation, senescence was also early, resulting in yield loss in both varieties.
Keywords: Harvest index; Humid tropics; Phenology; Senescence; Sprouting